Pathogenicity and virulence of African trypanosomes: From laboratory models to clinically relevant hosts - Liam J. Morrison; Pieter C. Steketee; Mabel D. Tettey; Keith R. Matthews (Virulence, 2023)
African trypanosomes are vector-borne protozoa, which cause significant human and animal disease across sub-Saharan Africa, and animal disease across Asia and South America. In humans, infection is caused by variants of Trypanosoma brucei, and is characterized by varying rate of progression to neurological disease, caused by parasites exiting the vasculature and entering the brain. Animal disease is caused by multiple species of trypanosome, primarily T. congolense, T. vivax, and T. brucei. These trypanosomes also infect multiple species of mammalian host, and this complexity of trypanosome and host diversity is reflected in the spectrum of severity of disease in animal trypanosomiasis, ranging from hyperacute infections associated with mortality to long-term chronic infections, and is also a main reason why designing interventions for animal trypanosomiasis is so challenging. In this review, we will provide an overview of the current understanding of trypanosome determinants of infection progression and severity, covering laboratory models of disease, as well as human and livestock disease. We will also highlight gaps in knowledge and capabilities, which represent opportunities to both further our fundamental understanding of how trypanosomes cause disease, as well as facilitating the development of the novel interventions that are so badly needed to reduce the burden of disease caused by these important pathogens.